SOUTH-SOUTH COOPERATION: BRAZILIAN PARTNERSHIP WITH MOZAMBIQUE AND THE CONSTRUCTION OF AN AIDS DRUG PLANT - Follér, Maj-Lis (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The paper intends to clarify the Brazilian foreign policy concerning AIDS treatment in Africa. The building of an AIDS drug plant in Mozambique is the concrete example of the diplomatic evolution showed by Brazil in the past few years – evolution that is detailed in the present article.